Marketing Strategic for Hydroponic Vegetable Product to Improve Marketing Performance Base on Digital Technology - Miftah, Himmatul; Alfiah, Ananda; Kusumawati, Riny; Mubarokah, Syaima Lailatul; Pramartaa, Ikhsan Qodri; Susanti, Aishah Rini; Aidah, Yuyu (Universitas Komputer Indonesia, 2024)
Agriculture is one of the sectors that has been the backbone of human civilization since the beginning, undergoing major transformation along with technological. The hydroponic vegetable market continues to grow along with increasing demand for healthy and sustainable agricultural products. In this digital era, marketing strategies based on digital technology are the key to increasing visibility and sales of hydroponic vegetable products. The purpose of this study is to investigate different digital marketing tactics that may be used to enhance the marketing effectiveness of hydroponically grown vegetables. By examining digital marketing techniques like social media marketing and the use of e-commerce platforms, this research identifies effective ways to strengthen the market position of hydroponic vegetable products in the digital era. The study also highlights the important role digital technology plays in changing the way manufacturers interact with consumers, measure marketing performance, and develop long-term relationships with customers. It is believed that the research's conclusions would give hydroponic vegetable growers insightful information and marketing practitioners in optimizing their marketing strategies in this increasingly digital market